THE EFFECT OF BREAST CARE AND GYMNASTICS ON MOTHERS WITH LESS BREAST MILK PRODUCTION: A LITERATURE REVIEW - Rasulina Br Peranginangin; Mardiana Ahmad; Andi Nilawati Usman; Nur Aliya Arsyad (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: The low coverage of exclusive breastfeeding shows that not many mothers succeed in exclusive breastfeeding. In post-partum mothers often because the pain experienced after childbirth makes the mother lazy to breastfeed the baby; this can cause the production of breast milk to be uneventful due to lack of stimulation in the breast so that the oxytocin cycle is not smooth and causes breast milk not to come out. Objectives: This study aimed to find out the Effect of Breast Care and Gymnastics on Mothers with Less Breast Milk Production. Design: This research design is the study of literature by descriptive methods. Data Sources: Search articles using the Mendeley app with a period of 2017 to 2021 by entering the keyword